Differential Regulation of the Asthmatic Phenotype by the Aryl Hydrocarbon Receptor - Traboulsi, Hussein; de Souza, Angela Rico; Allard, Benoit; Haidar, Zahraa; Sorin, Mark; Moarbes, Vanessa; Fixman, Elizabeth D.; Martin, James G.; Eidelman, David H.; Baglole, Carolyn J. (Frontiers in Physiology, 2021)
The aryl hydrocarbon receptor (AhR) is a ligand‐activated transcription factor that regulates the metabolism of xenobiotics. There is growing evidence that the AhR is implicated in physiological processes such proliferation, differentiation and immune responses. Recently, a role of the AhR in regulating allergic asthma has been suggested, but whether the AhR also regulates other type of asthma, particularly occupational/irritant-induced asthma, remains unknown. Using AhR-deficient (Ahr-/-) mice, we compared the function of the AhR in the response to ovalbumin (OVA; allergic asthma) versus chlorine (Cl2; irritant-induced asthma) exposure. Lung inflammation and airway hyperresponsiveness were assessed 24h after exposure to Cl2 or OVA challenge in Ahr-/- and heterozygous (Ahr+/-) mice. After OVA challenge, absence of AhR was associated with significantly enhanced eosinophilia and lymphocyte influx into the airways of Ahr-/- mice. There were also increased levels of interleukin-4 (IL-4) and IL-5 in the airways. However, OVA-induced airway hyperresponsiveness was not affected. In the irritant-induced asthma model caused by exposure to Cl2, the AhR did not regulate the inflammatory response. However, absence of AhR reduced Cl2-induced airway hyperresponsiveness. Collectively, these results support a differential role for the AhR in regulating asthma outcomes in response to diverse etiological agents.